Woman and Rural Development: An Exploration of Balinese Women’s Involvement in Rural Homestay - Putu Ratih Pertiwi; I Wayan Sukma Winarya Prabawa (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2024)
Homestays have emerged as a crucial discussions issue in village development initiatives. The subject of women’s involvement in household business has enhanced the discussion of how their participation improves individual quality in social interactions and is equally vital in village development. This study investigates the role of homestays in empowering women in rural Balinese communities, specifically Ubud and Blimbingsari. Despite a patriarchal social structure, women are increasingly involved in homestay businesses. The research employs a qualitative approach, using primary data sources; collected through interviews with purposive sampling. This research found that homestay businesses play a pivotal role in empowering and encouraging female members of the Ubud and Blimbingsari communities, fostering their self-recognition within their families and society. Through regular management and training, these businesses have significantly advanced the skills of female hosts, particularly in areas such as room preparation, cooking, communication, and hospitality. While these efforts have been beneficial, there remains room for further empowerment beyond the current limitations, especially in decentralizing control within the Blimbingsari tourism committee